A Comparative Analysis of Domestic Violence Shelter Staff Perceptions Regarding Barriers to Services in Bosnia and Herzegovina and the United States. (August 2018) - Grubb, Jonathan A.; Muftić, Lisa R.
Service provision for domestic violence (DV) survivors has been a long-standing staple of shelters in the United States. Although shelter services provide numerous benefits for survivors, barriers tied to acquisition remain a pressing concern when combatting DV. Nevertheless, there has been minimal research exploring barriers to service acquisition on a cross-national level. As such, the current research cross-nationally examines perceptions of shelter staff regarding acquisition barriers as well as the effectiveness of local agencies to meet survivor needs and differences in populations served in the United States (specifically Texas) as well as in Bosnia and Herzegovina. Data collection stemmed from self-report surveys originally constructed in English and translated into Bosnian/Serbian/Croatian. Results underscored differences between populations served, perceptions of local agencies assisting survivors of DV, and barriers tied to cultural and financial concerns. Implications, limitations, and future directions are also discussed.